Heterotopic pregnancy: a catastrophic event - Gupta, Neena; Dwivedi, Seema; Arya, Sangeeta; Pande, Shefali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Heterotopic gestation, although common with assisted reproductive techniques, is very rare in natural conception. A high index of suspicion can help in timely diagnosis and appropriate intervention. We report a case of heterotopic pregnancy in a 25-year-old woman presenting with hemoperitoneum from ruptured tubal pregnancy with live intrauterine gestation at 12 weeks of amenorrhea, diagnosed on ultrasound examination.